The Kaggle book : data analysis and machine learning for competitive data science - Banachewicz, Konrad; Massaron, Luca (Birmingham : Packt Publishing, 2022)
Millions of data enthusiasts from around the world compete on Kaggle, the most famous data science competition platform of them all. Participating in Kaggle competitions is a surefire way to improve your data analysis skills, network with an amazing community of data scientists, and gain valuable experience to help grow your career.
Includes index.
Buku bacaan asas fakulti
Keywords: Machine learning; Big data